House of Restorative Justice as a Forum of Actualizing the Nation’s Culture in Solving Criminal Cases - Kuntadi, Kuntadi (Faculty of Law, Universitas Jenderal Soedirman, 2022)
House of Restorative Justice is a follow-up to the existence of the Prosecutor’s Regulation of the Republic of Indonesia Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice. The establishment of this house aims to be a forum for meeting victims, perpetrators in resolving criminal cases that also involve traditional, community and religious leaders in exploring the values of local wisdom to perfect the application of positive law in the implementation of the termination of prosecution based on the Prosecutor’s Ragulation Number 15 of 2020. This research is a legal socio research that has the nature of descriptive and analytical research. The urgency of the establishment of the House of RJ is to explore the values of local wisdom contained in the community Restorative justice is in line with the legal values that live in Indonesian society (living law). The implementation of local wisdom values in resolving cases at the House of RJ. Currently, it is still only based on the settlement method, namely by using deliberation for consensus, but in this study, the prosecution in Toba Samosir and Kajang has accommodated local customary values and laws. Hence, in this case, the law and values of local wisdom can be used as a complement in the implementation of positive law enforcement.Keywords: House of Restorative Justice; Restorative Justice; criminal law; local wisdom; law enforcement.